Population Pharmacokinetics and Initial Dose Optimization of Sirolimus Improving Drug Blood Level for Seizure Control in Pediatric Patients With Tuberous Sclerosis Complex - Xiao Chen; Dongdong Wang; Lin Zhu; Jinmiao Lu; Yidie Huang; Guangfei Wang; Yiqing Zhu; Qiaofeng Ye; Yi Wang; Hong Xu; Zhiping Li (Frontiers Media S.A., 2021)
The purposes of this study were to explore the population pharmacokinetics and initial dose optimization of sirolimus improving drug blood level for seizure control in pediatric patients with tuberous sclerosis complex (TSC). Eighty pediatric patients diagnosed with TSC-related epilepsy were included for analysis. Sirolimus concentrations, physiological and biochemical indexes, and drug combination were collected to build a nonlinear mixed effect (NONMEM) model. Initial dose optimization was simulated by the Monte Carlo method. The weight and concomitant medication of oxcarbazepine affected sirolimus clearance. Without oxcarbazepine, for once-daily sirolimus regimen, the doses of 0.07, 0.06, 0.05, 0.04, and 0.03 mg/kg/day were recommended for weights of 5-7.5, 7.5-11.5, 11.5-19, 19-40, and 40-70 kg, respectively; for twice-daily sirolimus regimen, the doses of 0.05, 0.04, and 0.03 were recommended for weights of 5-8, 8-20, and 20-70 kg, respectively. With oxcarbazepine, for once-daily sirolimus regimen, the doses of 0.09, 0.08, 0.07, 0.06, 0.05, and 0.04 mg/kg/day were recommended for weights of 5-7.5, 7.5-10, 10-13.5, 13.5-20, 20-35, and 35-70 kg, respectively; for twice-daily sirolimus regimen, the doses of 0.06, 0.05, 0.04, and 0.03 were recommended for weights of 5-7, 7-14.5, 14.5-38, and 38-70 kg, respectively. The present study was the first to establish a population pharmacokinetic model of sirolimus improving drug blood level for seizure control in pediatric patients with TSC and recommend the initial dosage regimen.